Teacher multimodal feedback: Investigating students’ preferences and voices - Teguh Sulistyo; Agus Sholeh; Nara sari (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
This present study highlights the implementation of teacher multimodal feedback provision in speaking classes, especially students’ preferences and voices after obtaining teacher feedback. Teacher multimodal feedback was implemented in one semester (14 weeks) in two speaking classes with 36 students majoring English Language Department of a university in Malang, Indonesia. A questionnaire using a 4 Likert scale and an open-ended option was distributed to all respondents, and an in-depth interview was conducted with ten of them where five students represented each class. The data which were analyzed quantitatively indicate that students have different preferences in receiving teacher feedback, and they believe that teacher multimodal feedback is beneficial to improve their L2 oral productions. Direct feedback is the type they like most, but interruption is the mode of feedback they hate most. Some indications also suggest that teachers need to construct positive teacher-student social relationships in the classrooms. Some implications are also discussed.